Singing in Russian: A Guide to Language and Performance - Olin, Emily (Rowman & Littlefield Publishers, 2012)
With its unique blend of eastern and western traditions of music and poetry, the world of Russian vocal music is rich in spirituality, intimacy, and passion for singers and their audience. Russian song traditions offer an ideal opportunity for self-expression and the forging of a deep connection with one’s listeners. It also presents formidable challenges to singers at every level, ranging from the complexities native to sung and spoken Russian to the intricacies of diction and interpretation that lie behind the nuanced relationship between Russian music and poetry. Founded on the underlying principle that sung language differs dramatically from spoken language, Singing in Russian offers a comprehensive and accessible approach to understanding, mastering, and performing Russian vocal music. After covering the basics of the Cyrillic alphabet and Russian grammar and diction, author Emily Olin encourages readers to take the innovative step of using the music itself to guide the singer’s pronunciation and interpretation. English sound comparisons, linguistic and musical examples, and multifaceted exercises complement textual explanations, reinforcing the techniques Olin has employed for over three decades. The addition of repertoire lists and practical recommendations further equip singers to confidently go from start to stage. Furthermore, the online audio examples contain exercises that demonstrate and reinforce the correct sound and interpretation of everything from the alphabet to the presentation of vowels, consonants, words, and phrases.These can be found at: https://soundcloud.com/user-869634200/sets/singing-in-russian-a-guide-to-language-and-performance Singing in Russian is an invaluable resource for students, performers, teachers, directors, conductors, and coaches seeking to increase their access to Russian opera and art song, master the challenges they present to performance, and expand their personal, professional, and institutional repertoire on stage.